Emerging security challenges: American jihad, terrorism, civil war, and human rights - Choi, Seung-Whan (Praeger security international, 2018)
Introduction -- American jihad, Muslim Americans, and the general public -- America's homegrown jihadists and foreign fighting -- Democracy, civil liberties, and terrorism -- Theory of terrorist outbidding and its empirical evidence -- The effect of economic growth on terrorism -- New findings on the causes and effects of human rights violations -- Demystifying the impact of naming and shaming -- Preferential trade agreements and human rights abusers -- Leaders' education, democracy, and use of torture -- Civil war and rule of law -- Civil war, volunteer soldiers, and the military -- Conclusion